Air Pollution Exposure Impairs Airway Epithelium IFN-β Expression in Pre-School Children - Bonato, Matteo; Gallo, Elisa; Turrin, Martina; Bazzan, Erica; Baraldi, Federico; Saetta, Marina; Gregori, Dario; Papi, Alberto; Contoli, Marco; Baraldo, Simonetta (Frontiers in Immunology, 2021)
Introduction: air pollution is a risk factor for respiratory infections and asthma exacerbations. We previously reported impaired Type-I and Type-III interferon production (IFN-/) from airway epithelial cells of preschool children with asthma and/or atopy. In this study we analyzed the association between rhinovirus-induced IFN-/ epithelial production and acute exposure to the principal outdoor air pollutants in the same cohort. Methods: we studied 34 children (17asthmatics/17non-asthmatics) undergoing fiberoptic bronchoscopy for clinical indications. Bronchial epithelial cells were harvested by brushing, cultured and experimentally infected with Rhinovirus Type 16 (RV16). RV16-induced IFN- and production was measured by quantitative real time PCR. The association between IFNs production and the mean exposure to PM10, SO2 and NO2 in the day preceding bronchoscopy was evaluated using a Generalized Linear Model (GLM) with Gamma distribution. Results: acute exposure to PM10 and NO2 was negatively associated to RV16-induced IFN mRNA. For each increase of 1ug/m3 of NO2 we found a significative decrease of 2.3x103 IFN-β mRNA copies and for each increase of 1ug/m3 of PM10 a significative decrease of 1x103 IFN-β mRNA copies. No significant associations were detected between IFN-mRNA and NO2 nor PM10. Increasing levels of NO2 (but not PM10) were found to be associated to increased RV16 replication. Conclusions: short-term exposure to high levels of NO2 and PM10 is associated to a deficient production of INF-β by airway epithelium, which may lead to increased viral replication. These findings suggest a potential mechanism underlying the link between air pollution, viral infections and asthma exacerbations.